Reconstruction of the skull inverting the deformed surface of the bone after exeresis of a frontal arachnoid cyst - Jorge Felix Companioni Rosildo; Rita de Cassia Santa Barbara (University of São Paulo, 2017)
Intracranial arachnoid cysts need to be operated on when they are causing symptoms and aesthetic problems. The aim of this case report was to describe a new method of reconstructing the skull by eliminating a left frontal bone deformity by turning the inside out and the outside inward, which provided good aesthetics and protected the region of surgical interest after the removal of an arachnoid cyst of the left frontal lobe